Раскопки городища Китея - Молев, Е.А.; Сон, Н.А. (Археологічні дослідження в Україні, 2010)
Results of the research of Bosporan city Cytae in 2009 are presented. Search for the western line of a rampart was made, and an additional data testifying for the existence of a sacral complex from the 4th c. BC to the 5th—6th c. AD was obtained.